2017
DOI: 10.1002/cctc.201701133
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Synthesis of Rhodium–Palladium Alloy Nanocatalysts

Abstract: The chemistry of metastable RhPd alloys is not well understood, and well‐characterized nanoparticle (NP) examples remain rare. Well‐defined and near‐monodisperse RhPd NPs were prepared in a simple one‐pot approach by using microwave‐assisted or conventional heating in reaction times as short as 30 s. The catalytic hydrogenation activity of supported RhPd NP catalysts revealed that short synthesis times resulted in the most‐active and most‐stable hydrogenation catalysts, whereas longer synthesis times promoted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
1
21
1
Order By: Relevance
“…In our previous studies, we found that on close-packed surfaces, triatomic ensembles with three-fold symmetry are the smallest units for H and O adsorptions ( Fig. 1), [6][7][8][9]32 which most directly determine the adsorption environment; the atoms outside the triatomic ensemble are less important. 6,8,9,22 Therefore, adsorption is described in terms of the makeup of the triatomic ensemble in this paper.…”
Section: B Modeling Detailsmentioning
confidence: 84%
See 1 more Smart Citation
“…In our previous studies, we found that on close-packed surfaces, triatomic ensembles with three-fold symmetry are the smallest units for H and O adsorptions ( Fig. 1), [6][7][8][9]32 which most directly determine the adsorption environment; the atoms outside the triatomic ensemble are less important. 6,8,9,22 Therefore, adsorption is described in terms of the makeup of the triatomic ensemble in this paper.…”
Section: B Modeling Detailsmentioning
confidence: 84%
“…30 It has been widely accepted that the tuning of adsorption energies on the alloy surface can be explained by a shift of the electronic d-band center due to ligand and strain effects, 12 as well as linear interpolation models to describe ensemble effects. 10 However, it was recently found that although linear interpolation can roughly predict the binding energies of some adsorbates [e.g., O and S on the PdAu(111) surface alloy 10,31 ], it fails to explain the binding energies of other species (e.g., H on PtAu, IrAg, and PdRh, 17,32,33 and OH on PtAu, IrAu, PdAg, PtAg, and IrAg 6 ) due to different tunability properties of specific surface ensembles. With only a few theoretical studies attempting to distinguish these different effects for a description of adsorption on alloy surfaces, 10,11 we are motivated to disentangle them here.…”
Section: Introductionmentioning
confidence: 99%
“…5,11,28−30 However, the former case is difficult to predict from first-principles, while the latter often results in materials with poor atomic ordering. 4,5,31,32 Hence, conventional synthetic methods, such as high-temperature annealing and/or colloidal synthesis, largely exclude the formation of metastable ordered intermetallic compounds under typical reaction conditions. 31,33−35 Electrochemical deposition has recently emerged as a flexible technique for the direct preparation of metastable alloys and ordered intermetallic phases, yielding materials which can possess high intrinsic catalytic performance.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] The adaptability and the catalytic efficiency of these nanosystems can be further enhanced by alloying two or more metallic species, which structural and electronic properties are significantly different from those of the individual constituents. [7][8][9][10][11][12] Furthermore, at the nanoscale it is possible to alloy bulk-immiscible elements giving rise to new unexplored compounds, as in the case of gold-rhodium nanoalloys. According to literature, gold and rhodium are almost immiscible in bulk: the dissolution of the metals is below 1 % even when the temperature reaches 1200 K. [13,14] This is likely related to the intensity of metal-metal mutual interactions: homopolar interactions, especially for Au, [15] are stronger than heteropolar AuÀ Rh interactions.…”
Section: Introductionmentioning
confidence: 99%